IMPLEMENTATION OF ANDROID-BASED AUGMENTED REALITY IN ENGLISH EDUCATION - Oktadela, Resy; Shalawati, Shalawati; Elida, Yusti; Hadiyanti, Putri Octa; Ismail, Syofianis (English Review: Journal of English Education, 2024)
The aim of this study was to leverage augmented reality (AR) technology in enhancing English language learning, focusing on the development and evaluation of AR-based learning media for educational use, particularly at SD IT Imam Syafe’i. The study encompassed a comprehensive approach, starting with an analysis of existing educational tools to identify the need for AR in language learning, followed by the design and development of an AR framework tailored for English education. This process included expert evaluations and revisions to ensure the quality and effectiveness of the AR tools. The implementation phase involved testing the AR media in an educational setting and analyzing its impact on students' critical thinking and digital literacy through various quantitative methods. Finally, the study evaluated the practicality and user-friendliness of the AR learning media based on student feedback, aiming to provide insights and resources for educators and institutions interested in integrating advanced technology into their teaching practices, with potential applications extending to school-based and Islamic boarding school-based university environments.